Osteoid osteoma of the femoral head - Gupta, HK; Khare, KD (Journal of College of Medical Sciences-Nepal, 2012)
We present a rare case of intra-articular osteoid osteoma of the femoral head in the subarticular region in a 52 years old woman, treated with intralesional excision and bone grafting along with prophylactic internal fixation for impending stress fracture. At one year follow up, the patient has returned to her normal functional status. The patient was asymptomatic and without recurrence at one year follow up. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 45-48 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6680